Molecule engineering of coumarin to reverse aggregation-caused quenching: Facile access to BioAIEgens - Shouji Li; Xiaobin Li; Junyu Liu; Yuting Lin; Xuedan Zhang; Weiren Zhong; Juan Li; Caifa You; Dong Wang; Jisong Zhang; Xu Xu; Xu-Min Cai; et al. (iScience)
Summary: Aggregation-induced emission luminogens (AIEgens) have been extensively investigated and widely used in biomedical fields. However, AIEgens are mostly derived from petrochemicals, leading to challenges of renewability, sustainability, and biocompatibility. Therefore, it is of striking prospect to construct bioproduct-based AIEgens (BioAIEgens) based on the natural profits. Herein, we proposed a straightforward method named “rotor-alicyclic” strategy to prepare BioAIEgens with high fluorescence and produce reactive oxygen species (ROS) activities as well as high biosafety. We prepared four BioAIEgens by introducing two rotors and a naturally rigid alicyclic moiety into coumarin molecule. The aggregation-induced emission (AIE) performances were evaluated, especially the fluorescence and production of ROS activities. Mechanistic study proved that the introduction of two rotors can destroy the planar structure, and the rigid alicyclic moiety can limit the molecular motion. Furthermore, the biosafety was carefully investigated in vitro and in vivo, demonstrating the high biocompatibility. Summarily, we developed a facile engineering method to prepare BioAIEgens.